Theory of language in Peru in 19th century: Agents, keys of interpretation and conception of grammar - Zamorano Aguilar, Alfonso (Boletín de Filología, 2021)
In this article we analyze the theory of language through school grammar treatises published in Peru in 19th century, as a contribution to the study of linguistic ideas in Latin America. For this purpose, on the basis of the theories of the canon and the theory of textual series, and with an approach which combines the historiography of internal and external linguistics, we present the agents of this grammatical theory (grammarians and receivers of the works), the internal and external keys of interpretation of grammatical ideas in the nineteenth-century Peruvian context, as well as, finally, the conception of grammar and the underlying theoretical models in the twenty-four texts of the corpus.